Time to antiretroviral therapy initiation in HIV-positive patients with opportunistic infections/AIDS-defining illness in Southern Thailand: a prospective cohort study - Chanadda Wuttikul; Nattasiri Thanawuth; Malee Rojpibulsatit; Sutthiporn Pattharachayakul (HIV & AIDS Review. International Journal of HIV-Related Problems)
Introduction Rapid antiretroviral therapy (ART) initiation is recommended for all people living with human immunodeficiency virus (HIV). Time to ART initiation in individual patients depends on several factors. The study objectives were to investigate the time to ART initiation in HIV-positive patients with opportunistic infections/AIDS-defining illnesses (OIs/ADI), and associated factors.